2020
DOI: 10.1136/jech-2019-213399
|View full text |Cite
|
Sign up to set email alerts
|

Change in device-measured physical activity assessed in childhood and adolescence in relation to depressive symptoms: a general population-based cohort study

Abstract: AimEvidence for a link between physical activity and mental health in young people is hampered by methodological shortcomings. Using repeat assessments of device-measured physical activity, we examined the association of within-individual variation in free-living activity over 7 years with depressive symptoms.MethodsThis was a prospective cohort study of a nationally representative sample of children born in the UK (n=4898). Physical activity was quantified using accelerometry at ages 7 and 14. The main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In line with other studies (Doré et al, 2019 ; Loewen et al, 2019 ; Gómez-Baya et al, 2020 ; Wu et al, 2021 ), the findings indicated that higher levels of PA in childhood can predict mental health problems 6 years later in both boys and girls. This confirms a general tendency found in several studies with prepubertal children (Hamer et al, 2020 ). However, for the cross-lagged association from Wave 1 to Wave 2 (i.e., during adolescence), there was no significant path from PA to mental health problems neither for boys nor girls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with other studies (Doré et al, 2019 ; Loewen et al, 2019 ; Gómez-Baya et al, 2020 ; Wu et al, 2021 ), the findings indicated that higher levels of PA in childhood can predict mental health problems 6 years later in both boys and girls. This confirms a general tendency found in several studies with prepubertal children (Hamer et al, 2020 ). However, for the cross-lagged association from Wave 1 to Wave 2 (i.e., during adolescence), there was no significant path from PA to mental health problems neither for boys nor girls.…”
Section: Discussionsupporting
confidence: 92%
“…Several longitudinal studies showed a long-term relationship between PA and psychological constructs, but the results are inconsistent (Wu et al, 2018 , 2021 ; Doré et al, 2019 , 2020 ; Kleppang et al, 2019 ; Loewen et al, 2019 ; Gómez-Baya et al, 2020 ; Hamer et al, 2020 ; Isaksson et al, 2020 ; Kandola et al, 2020 ; van Woudenberg et al, 2020 ; Bowe et al, 2021 ). To illustrate some results, Nigg et al concluded that PA may not be a preventive component for mental health problems, but mental health problems can be a risk factor for lower activity at preadolescent ages (Nigg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It inevitably led to lower levels of PA, and prolonged sedentary screen time. Insufficient PA level of adolescents was associated with increased anxiety level, decreased learning efficiency and increased risk of depression [20]. Research has approved that increase in SED resulted in poor mental health [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews consistently note that higher levels of physical activity are associated with better mental health among youth (e.g., lower anxiety symptoms, lower depressive symptoms) [ 32 , 33 ]. For example, youth aged 7 and 14 years who met the 60 min/day of MVPA guideline had lower risk of depression [ 34 ]. There is evidence that both regular physical activity and limited screen time have mental health benefits among youth [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%